PENGARUH KONDISI KEUANGAN, RISIKO KEUANGAN, DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Faizal Agung Rahmadani; Putu Prima Wulandari (UNHI Press, 2022)
Abstract: This study aims to determine the effect of financial condition, financial risk, and company growth on the company value of retail companies listed on the Indonesia Stock Exchange from 2019 to 2021. The variables of this study involve financial condition, financial risk, company growth, and company value with the proxies of the Zmijewski model, debt to equity ratio, investment opportunity set, and Tobin's Q respectively. The samples selected through purposive sampling include 99 data from 33 companies between 2019 and 2021, and are analysed by multiple linear regression utilizing SPSS 25 software. The results of this study indicated that financial condition had no effect on company value, financial risk had no effect on company value, and company growth had a positive effect on company value.